Analisis Pembelajaran Geometri Siswa Sekolah Dasar - Rahayu, Eka; Hidayatillah, Wahyu (LP3M UNZAH GENGGONG, 2020)
ABSTRACT This study aims to determine how the geometry learning process of students in elementary schools. The research method used is a qualitative approach with descriptive research type. The research subject was a teacher at Tunjung Sekar 2 Elementary School Malang City. Data collection techniques used by interviews related to learning methods, media and student difficulties. Data analysis was carried out by describing the results of the interview. The results obtained are that the teacher uses various methods according to the conditions of learning and the material presented. The media used is very simple, namely concrete objects that are around students and teachers to make students experience for themselves. Difficulties often encountered by students are weak in multiplication and division, geometric concepts and story problems. Things that teachers do to overcome student difficulties include enrichment and remedies, working with parents and before entering class in the morning, literacy and memorizing multiplication are held. Students' mathematics achievement on average has increased after applying some of these solutions. The activity and learning outcomes of male and female students did not experience any differences. The difference can be seen from the aspect of persistence where female students are more diligent than male students. Keywords: learning geometry, learning methods and media, student difficulties